Deoxygenation of tertiary amine N-oxides under metal free condition using phenylboronic acid - Gupta S.; Sureshbabu P.; Singh A.K.; Sabiah S.; Kandasamy J. (My University, 2025)
A simple and efficient method for the deoxygenation of amine N-oxides to corresponding amines is reported using the green and economical reagent phenylboronic acid. Deoxygenation of N,N-dialkylaniline N-oxides, trialkylamine N-oxides and pyridine N-oxides were achieved in good to excellent yields. The reduction susceptible functional groups such as ketone, amide, ester and nitro groups are well tolerated with phenylboronic acid during the deoxygenation process even at high temperature. In addition, an indirect method for identification and quantification of tert-amine N-oxide is demonstrated using UV–Vis spectrometry which may be useful for drug metabolism studies. © 2017 Elsevier Ltd